Picturing Pasargadae: Visual Representation and the Ambiguities of Heritage in Iran - Mozaffari, Ali (2017)
This paper probes the relationship between visual representations and visitation practices at Pasargadae, a UNESCO World Heritage site in southern Iran. Presenting a systematic analysis of publicly available online images of Pasargadae, the paper examines the complex relationship between the place and its visual representations. Through analysis, the paper elaborates on a sense of intimacy that, while grounding Pasargadae, is also a potential common ground in pre-Islamic heritage in which the Iranian state and society could at once meet and contest versions of identity. Examining this relationship facilitates reflections into both heritage and the peculiarities of its visual representation in the Iranian context.